Evaluation of Acute Kidney Injury and Its Risk Factors in Children Admitted with Diagnosis of Nephrotic Syndrome: Acute Kidney Injury in Nephrotic Syndrome - Kumari, Anita; Sahai, Lehar; kumar, Sanjay; Bhatnagar, Ruchika (Journal of Pediatric Nephrology, 2021)
Background and Aim: Acute Kidney Injury (AKI) is an important complication of Nephrotic Syndrome (NS) associated with adverse outcomes. The frequency of AKI has increased to almost double in the last decade. This study was conducted to determine the incidence of AKI, risk factors, and its association with outcomes in hospitalized children with NS. Methods: All children aged 1-18 years with a diagnosis of NS from 01 November 2018 to 31 May 2020 were enrolled in the study. AKI was diagnosed using the KIDIGO 2012 guidelines and classified according to the pediatric RIFLE definition. Results: The mean age of the children was 4.7± 2.8 years. Complications were observed in 67% of the cases. The most frequent complication was anemia (25%) followed by infection (21%). The incidence of AKI was 18.6% in hospitalized children with NS. According to the pRIFLE criteria, 11.6% of the children met stage 1 (risk) criteria, 4.6% met stage 2 (injury) criteria, and 2.3% met stage 3 (failure) criteria. Among all NS children, 53% received nephrotoxic drugs during the hospital stay. On applying multivariate logistic regression analysis, only male gender, associated anemia, and vancomycin use were significant independent risk factor for AKI in nephrotic syndrome patients. Conclusion: AKI is more frequent in the first episode of NS rather than in any type of relapses. Although nephrotoxic drugs and male gender are known independent risk factors for development of AKI, associated anemia is still not considered as an independent risk factor for AKI in children with NS.